A Missing Link Between Job Autonomy and Unethical Behavior - Ambreen Ahmed; Aamir Firoz Shamsi; Mudassar Aziz (ETIKONOMI, 2020)
The purpose of this paper is to theoretically address a surprising omission in literature by proposing a cognitive mechanism that sanctions individual-level unethical behaviors. This secondary literature-based qualitative study fills a theoretical gap by employing an extensive review of substantive empirical and theoretical literature of the last 15 years. However, those who consider their moral identity necessary for their self-concept are less likely to behave unethically. This proposed process, along with the path suggested by previous studies, in which individuals are having job autonomy feel unconstrained by rules before engaging in unethical behaviors. So, it proposes an underlying cognitive mechanism between job autonomy and unethical behavior. This study implies that it clarifies job autonomy’s role in promoting the negative outcome of employees’ unethical behaviors and informs organizational policymakers about the importance of satisfying the need for job autonomy.JEL Classification: D23, M12, M51, O15How to Cite:Ahmed, A., Shamsi, A. F., & Aziz, M. (2020). A Missing Link Between Job Autonomy and Unethical Behavior. Etikonomi: Jurnal Ekonomi, 19(1), 95 – 118. https://doi.org/10.15408/etk.v19i1.12391.